2012
DOI: 10.1097/adm.0b013e318233d637
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction as an Important Predictor in Early Detection of Adolescent Drug Use Experience—Implications for Research and Practice

Abstract: We present results from a cross-sectional study of the entire adolescent student population aged 14 to 18 years of the island of Kos, on the correlates between personality, illicit chemical substance use, and Internet abuse. Results demonstrate that adolescents who have used illicit substances and are abusing the Internet as well appear to share some common personality characteristics, namely those that are classified under the label of "psychoticism" in the Eysenck's personality model. An increase in the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 33 publications
6
48
0
5
Order By: Relevance
“…The sample sizes ranged from 1,270 in Greece [71,72] to 10,988 adolescents and young adults in China, aged 13-23 years [78] The same cut-off, i.e., endorsing a minimum of five out of eight diagnostic items, has been applied to a majority of these studies. Internet addiction prevalence rates ranged from 1.7% of boys and 1.4% of girls in a representative sample of Finnish adolescents [77] to 26.4% and 26.7% at wave one and wave two in a longitudinal sample of adolescent students in Hong Kong, respectively [73].…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample sizes ranged from 1,270 in Greece [71,72] to 10,988 adolescents and young adults in China, aged 13-23 years [78] The same cut-off, i.e., endorsing a minimum of five out of eight diagnostic items, has been applied to a majority of these studies. Internet addiction prevalence rates ranged from 1.7% of boys and 1.4% of girls in a representative sample of Finnish adolescents [77] to 26.4% and 26.7% at wave one and wave two in a longitudinal sample of adolescent students in Hong Kong, respectively [73].…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
“…In eleven studies, the IADQ [13] was used to assess Internet addiction in adolescents [68][69][70][71][72][73][74][75][76][77][78]. The sample sizes ranged from 1,270 in Greece [71,72] to 10,988 adolescents and young adults in China, aged 13-23 years [78] The same cut-off, i.e., endorsing a minimum of five out of eight diagnostic items, has been applied to a majority of these studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive vulnerability coding approach or content analysis of verbatim explanations (CAVE) was developed in 1984 by Seligman and colleagues [32]. The coding approach assesses cognitive vulnerabilities which may be a precursor for depression symptoms [33]. In this coding approach, each text disclosure is examined for both an event and attribution, which are then categorized as internal versus external, global versus specific, and stable versus unstable.…”
Section: Future Codebook Developmentsmentioning
confidence: 99%
“…Finally, based on many research works, it is observed that internet technology is more entertaining, interesting, interactive, pleasant experience, and enjoyable. This can be claimed in persons with CP who are addicted to the internet [33].…”
Section: Discussionmentioning
confidence: 99%